National Guard Service Member Reintegration Experiences: The Transition Back Home. (3rd July 2018) - Sripada, Rebecca K.; Walters, Heather; Forman, Jane; Levine, Debra S.; Pfeiffer, Paul N.; Bohnert, Kipling M.; Emerson, Lauren; Valenstein, Marcia
ABSTRACT: As citizen-soldiers who maintain military and civilian roles, National Guard service members may experience unique challenges during reintegration. In the current study, 78 Operation Enduring Freedom/Operation Iraqi Freedom National Guard service members completed semistructured interviews on their reintegration experiences. Many soldiers reported smooth reintegration experiences, but others reported challenges. When soldiers reported mental health issues, they usually reported anger problems and alcohol misuse. Help seeking was not frequently reported. The findings highlight the complex interactions among reintegration domains, particularly the influence of family members on help-seeking. Continued efforts are needed to facilitate service delivery and promote smooth reintegration experiences among National Guard service members.